Dynamic asymmetric strain imprinted into substrates by an oxide thin film - Elliot Kisiel; Alexandre Pofelski; Pavel Salev; Erbin Qiu; Spencer Reisbick; Chuhang Liu; Andreas Glatz; Ishwor Poudyal; Wei He; Rourav Basak; Kaan Alp Yay; Junjie Li; et al. (Science, 2026)
In film-substrate systems, the substrate role is often considered to be limited to providing static mechanical constraints. Dynamic film-substrate interactions when a structural change in the film modifies the substrate are generally disregarded. Using combined x-ray and electron microscopies, we observed that an electrically induced filament in a vanadium dioxide film created strong asymmetric strain in an underlying sapphire substrate. This asymmetric substrate strain fed back into the film and defined the filament expansion direction, revealing the importance of film-substrate dynamic interactions in determining film functionality. Furthermore, the strain imprint propagated at least tens of micrometers deep into the substrate, exceeding the film thickness by more than 200-fold, potentially enabling substrate functionalization as an active mechanical coupling media in three-dimensional integrated microelectronic architectures.